Time to Empower Release of Insects Carrying a Dominant Lethal and Wolbachia Against Zika. (19th May 2016) - Dickens, Borame L.; Yang, Jie; Cook, Alex R.; Carrasco, Luis R.
Abstract: RIDL (release of insects with dominant lethality) and Wolbachia are 2 potentially powerful tools in the fight against Zika, but their technological advancement is being hampered by policy barriers. In this study, we discuss what could be done to overcome these regulatory deadlocks.